Quality and productivity in comminution of small-diameter tree bundles. Issue 3 (1st September 2016) - Nuutinen, Yrjö; Petty, Aaron; Bergström, Dan; Rytkönen, Matleena; Di Fulvio, Fulvio; Tiihonen, Ismo; Lauren, Ari; Dahlin, Bo
ABSTRACT: Bundling small-diameter trees from thinnings has become a viable technology with the development of the Fixteri harvester-bundler. Several studies have measured the productivity of the machine, however, bundling also influences the whole supply chain. A study was conducted to investigate the quality of chips and productivity of five different conventional chippers and one grinder when comminuting bundles produced of small-diameter trees. The productivity based on dry mass was on average 44.8 tonne per effective working hour (E0 H −1 ), and varied considerably between the machines; 1:2.3 being the observed relation between lowest and highest performance of machines. Productivity when comminuting bundles was 1.5–3.2 times higher than normally found in the literature for unbundled (loose) material. The quality of the produced fuel chips varied between machines in dry weight share of particle sizes <3.15 mm from around 5 to 35%. The average size of the chips varied between 5 and 20 mm. The study indicated that productivity and quality of fuel chips are dependent on machine type and the raw material processed. Further investigations should examine different machine systems in designed experiments where e.g. several assortments and operational environments are included.